Citrullination: the loss of tolerance and development of autoimmunity in rheumatoid arthritis - G. Ferraccioli; B. Tolusso; I. Cuoghi; A.L. Fedele; S. Alivernini (PAGEPress Publications, 2011)
Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by synovial inflammation and pannus formation, which can lead to severe destruction of cartilage and bone. Several self proteins have been suggested to be disease-driving autoantigens. Moreover the presence of autoantibodies to citrullinated proteins in sera of patients with RA enhances the strength of this hypothesis. Proteins are encoded by a limited number of genes in our genome. Post-translational modifications such as phosphorylation, glycosylation and citrullination can increase the morphological and the functional diversity of the proteome.